2015
DOI: 10.1038/nn.4090
|View full text |Cite
|
Sign up to set email alerts
|

Coordinated forms of noradrenergic plasticity in the locus coeruleus and primary auditory cortex

Abstract: The cerebral cortex is plastic and represents the world according to the significance of sensory stimuli. However, cortical networks are embodied within complex circuits including neuromodulatory systems such as the noradrenergic locus coeruleus, providing information about internal state and behavioral relevance. While norepinephrine is important for cortical plasticity, it is unknown how modulatory neurons themselves respond to changes of sensory input. Here we examine how locus coeruleus neurons are modifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

11
208
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 207 publications
(230 citation statements)
references
References 49 publications
(50 reference statements)
11
208
0
Order By: Relevance
“…During the critical period, enhancement of sensory input to the cortex might then occur by a reduction of spontaneous excitatory activity by GABAergic neuron maturation accompanying a broadband boosting of responses to stimuli that activate the adrenergic system. Martins and Froemke (2015) provide support for this idea behaviorally and electrophysiologically by showing that in adult A1, pairing sounds with LC stimulation leads to a transient broadening of frequency tuning followed by a longlasting sharpening at the paired sound frequency. It is likely that NE comodulates such processes along with other neuroNeuro Forum modulators like ACh; however, Shepard et al (2015) indicate that NE exhibits a unique, necessary role in auditory cortex plasticity.…”
mentioning
confidence: 59%
See 3 more Smart Citations
“…During the critical period, enhancement of sensory input to the cortex might then occur by a reduction of spontaneous excitatory activity by GABAergic neuron maturation accompanying a broadband boosting of responses to stimuli that activate the adrenergic system. Martins and Froemke (2015) provide support for this idea behaviorally and electrophysiologically by showing that in adult A1, pairing sounds with LC stimulation leads to a transient broadening of frequency tuning followed by a longlasting sharpening at the paired sound frequency. It is likely that NE comodulates such processes along with other neuroNeuro Forum modulators like ACh; however, Shepard et al (2015) indicate that NE exhibits a unique, necessary role in auditory cortex plasticity.…”
mentioning
confidence: 59%
“…During cortical plasticity events, NE may shift excitatory/inhibitory balance by exerting a disinhibitory influence on the circuitry. In support of this idea, Martins and Froemke (2015) have shown that in adult primary auditory cortex (A1), disinhibition by LC activation permits BF tuning plasticity. From a developmental standpoint, these effects of NE may function in the background of maturing GABAergic inhibition.…”
mentioning
confidence: 83%
See 2 more Smart Citations
“…It has been shown that LC is highly plastic and responds to sensory stimulation including auditory stimulation (Snow et al 1999;Martins and Froemke 2015). Indeed, there is coupling between LC and somatosensory-evoked activity (Safaai et al 2015).…”
Section: Enhancing Sensory Function In Osamentioning
confidence: 99%